Why there is no German "Masdar City" - Environmental and ecological aspects in Germany's urban development. - Zwicker-Schwarm, Daniel (My University, 2014)
The article describes which role ecology and environmental issues play in Germany's urban development and how they are reflected in its legal framework and policy programmes. It starts with a description of past and present challenges of urban planning and the role of the local level within environmental policy implementation. It then gives an outline of important fields of action - sustainable land use, green infrastructure, mitigation of climate change, and mobility - and describes the policy instruments in place and how they are implemented in exemplary urban projects. A special focus is given to integrative approaches that focus on a combination of environmental, economic and social aspects. The conclusion identifies some lessons learnt for incorporating environmental issues in urban development in better ways.
Keywords: Stadtentwicklungsplanung; Ökologie; Stadtökologie; Stadtentwicklung; Flächennutzung; Grünflächenplanung; Industriepark; Energieeinsparung; Mobilität; Beispielsammlung; Nachhaltige Entwicklung; Ökologische Stadterneuerung; Energetische Modernisierung; Klimaschutzmaßnahme; Nachhaltige Mobilität